DEVELOPMENT OF COMIC-BASED MATHEMATICS LEARNING MEDIA ON MATERIAL OF 3D CUBE SIDE WITH A SCIENTIFIC APPROACH FOR 9TH GRADE SMP/MTS - Rizki Dera Amanda; Suhendra Suhendra; Syariful Fahmi (FKIP Universitas Muhammadiyah Tangerang, 2026)
Math subjects are subjects that are often difficult for learners. Poor media and learning resources during the learning process greatly influence the results of learning. A varied medium of learning is urgently needed to help the learning process. One of the learning media that can help the learning process is the comic-based learning medium. The study aims to develop a comic-based medium of learning-room material that is particularly worthy of use in the learning process. The study is a development study using addie's model: analysis, design, development, improvement, and design. The subject of this study is a material expert, a media expert, and students of SMPN 2 Mendo Barat. The data-collection techniques used in the study include interviews, questionnaires, and observations. The data obtained from the questionnaire were analyzed descriptively qualitative and quantitative. As a result of the study, the developed media of learning is deemed to be particularly useful in the mathematical learning process. This is shown with the result of a dose of the learning media This is demonstrated by the overall assessments of the learning media and get an excellent category by an average of 3.60. Each assessment results from a material expert who got an excellent category with an average of 3.50, from a media expert who got an excellent category with an average of 3.88, from a learner's response that got an excellent category with an average of 3.38 in the small class trials and 3.64 in the large class trials.